Building future primary teachers' capacity in STEM: based on a platform of beliefs, understandings and intentions - Premnadh M. Kurup; Xia Li; Greg Powell; Michael Brown (SpringerOpen, 2019)
Abstract Background STEM education needs to begin in primary schools and should aim to prepare young people for active participation in their future. To produce a generation interested and skilled in STEM, the key foci within schools may best occur through teams of teachers working together in an integrated approach, based on cross-curricular teaching and learning. Teachers play a key role in STEM education, and it is important to attract high achievers with relevant backgrounds into teaching. This research study focused on the beliefs, understandings, and intentions of pre-service primary teachers to teach STEM. These beliefs, understandings, and intentions form the platform on which the pre-service teachers build their capacity to teach STEM subjects in primary schools. Results The data (n = 119) collected from a designed questionnaire were analysed qualitatively and quantitatively. An interpretive practice has been used in formulating categories based on responses regarding beliefs, understandings, intentions, and ideal scenarios for future practices and a grounded theory approach for formulating scenarios based on data analysis. The qualitative data were coded into categories based on responses. Structural equation modelling (SEM) and logical regression were conducted to find relationships of the pre-service teacher's platform for capacity building and connecting to what is required in their classrooms now and in the future. Logistic regressions were used to explore the association of all the questionnaire items and open responses related to the platform and future capacity building. Based on the results, it is evident that the platform developed for teaching STEM based on experience in their teaching degree is limited; however, they have positive intentions to take up STEM. They are not seeing any positive initiative at schools, and they have limited confidence to teach STEM. However, they were suggesting that they should be provided with more opportunities to teach STEM. Conclusions Overall, our findings indicate that pre-service teachers do not have strong understanding; however, they have strong beliefs and intentions to teach STEM in their future career. The results of this study indicate that the capacity they have built provides them with explicit views on how to teach STEM in primary schools now and informs what they need for the future teaching of STEM. It is essential to formulate a course work and professional development in STEM, capable of integrating disciplines, providing an understanding of pedagogical approaches, and connecting to real-life relevance with the twenty-first century competencies.